The Effect of Interpersonal Counseling for Subthreshold Depression in Undergraduates: An Exploratory Randomized Controlled Trial. (22nd February 2018) - Yamamoto, Ami; Tsujimoto, Emi; Taketani, Reiko; Tsujii, Noa; Shirakawa, Osamu; Ono, Hisae
Abstract : Background. Subthreshold depression and poor stress coping strategies are major public health problems among undergraduates. Interpersonal counseling (IPC) is a brief structured psychological intervention originally designed for use in primary care to treat depressive patients whose symptoms arose from current life stress. Objectives. This study examined the efficacy of IPC in treating subthreshold depression and coping strategies among undergraduates in school counseling. Materials and Methods. We carried out an exploratory randomized controlled trial comparing the efficacy of IPC with counseling as usual (CAU). Participants were 31 undergraduates exhibiting depression without a psychiatric diagnosis. Results. The Zung Self-Rating Depression Scale total score decreased significantly in the IPC group (n = 15 ; Z = - 2.675, p = . 007 ), but not in the CAU group ( n = 16 ) . The task-oriented coping score of the Coping Inventory for Stressful Situations showed a tendency towards a greater increase in the IPC group than in the CAU group (t = 1.919, d f = 29, p = . 065 ). Conclusions. The IPC might be more useful for student counseling because it can teach realistic coping methods and reduce depressive symptoms in a short period. Further studies using more participants are required.